Amphiphilic anthanthrene trimers that exfoliate graphite and individualize single wall carbon nanotubes - Münich, Peter Wilhelm; Pfäffli, Matthias; Volland, Michel; Liu, Shi-Xia; Haener, Robert; Guldi, Dirk Michael (Nanoscale, 2020)
A phosphodiester-linked dialkynyl substituted anthanthrene trimer (1) has been designed and synthesized. Its graphene ribbon like structure is expected to facilitate interactions with nanographene (NG) and single wall carbon nanotubes (SWCNT) to yield novel and stable carbon-based nanomaterials. Interactions with trimer 1 lead to exfoliation of NG and to the individualization of SWCNTs. Phosphate groups, in general, and their negative charges, in particular, render the resulting nanomaterials soluble in ethanol, which is ecologically favourable over DMF required for the processing of pristine NG or SWCNTs. The newly formed nanomaterials were probed by complementary spectroscopic and microscopic techniques. Of particular importance were transient absorption and fluorescence excitation measurements, which revealed an efficient energy transfer within the carbon-based nanomaterials.
CRIS-Team Scopus Importer:2020-01-14

Azulenocyanines immobilized on graphene; On the way to panchromatic absorption and efficient DSSC blocking layers - Volland, Michel; Lennert, Annkatrin; Roth, Alexandra Marina; Ince, Mine; Torres, Tomas; Guldi, Dirk Michael (Nanoscale, 2019)
Herein, a novel electron donor-acceptor hybrid consisting of a NIR absorbing azulenocyanine as an electron donor and few-layer graphene as an electron acceptor was prepared. The extended aromatic core of azulenocyanine (1) assists in the exfoliation of graphite and allows the formation of a very high-quality few-layer graphene azulenocyanine hybrid system (2). The formation of a stable azulenocyanine/graphene hybrid was verified by means of an arsenal of spectroscopic and microscopic techniques. Notable is the fact that the absorption spectrum recorded for 1 and likewise that for 2 covers large portions of the solar spectrum, that is, from the UV through the visible to the NIR region. In light of the latter, we incorporated 1 as well as 2 as a photosensitizer in dye sensitized solar cells (DSSCs) and probed their light harvesting. Besides an increase in the photovoltaic conversion efficiency we focused on the stability of DSSCs by preventing charge recombination between FTO and the liquid electrolyte. We used 2 as a blocking layer and in comparison with a TiCl4 pretreated blocking layer a superior conversion efficiency was realized.
CRIS-Team Scopus Importer:2019-06-21

Chemical functionalization and characterization of graphene-based materials - Bottari, Giovanni; Angeles Herranz, Ma; Wibmer, Leonie; Volland, Michel; Rodriguez-Perez, Laura; Guldi, Dirk Michael; Hirsch, Andreas; Martin, Nazario; D'Souza, Francis; Torres, Tomas (Chemical Society Reviews, 2017)
Graphene-based materials (GBMs), with graphene, their most known member, at the head, constitute a large family of materials which has aroused the interest of scientists working in different research fields such as chemistry, physics, or materials science, to mention a few, arguably as no other material before. In this review, we offer a general overview on the most relevant synthetic approaches for the covalent and non-covalent functionalization and characterization of GBMs. Moreover, some representative examples of the incorporation into GBMs of electroactive units such as porphyrins, phthalocyanines, or ferrocene, among others, affording electron donor-acceptor (D-A) hybrids are presented. For the latter systems, the photophysical characterization of their ground- and excited-state features has also been included, paying particular attention to elucidate the fundamental dynamics of the energy transfer and charge separation processes of these hybrids. For some of the presented architectures, their application in solar energy conversion schemes and energy production has been also discussed. Graphene-based materials (GBMs), with graphene, their most known member, at the head, constitute a large family of materials which has aroused the interest of scientists working in different research fields such as chemistry, physics, or materials science, to mention a few, arguably as no other material before. In this review, we offer a general overview on the most relevant synthetic approaches for the covalent and non-covalent functionalization and characterization of GBMs. Moreover, some representative examples of the incorporation into GBMs of electroactive units such as porphyrins, phthalocyanines, or ferrocene, among others, affording electron donor-acceptor (D-A) hybrids are presented. For the latter systems, the photophysical characterization of their ground- and excited-state features has also been included, paying particular attention to elucidate the fundamental dynamics of the energy transfer and charge separation processes of these hybrids. For some of the presented architectures, their application in solar energy conversion schemes and energy production has been also discussed.

Complexation and Versatile Reactivity of a Highly Lewis Acidic Cationic Mg Complex with Alkynes and Phosphines - Pahl, Jürgen; Stennett, Thomas; Volland, Michel; Guldi, Dirk Michael; Harder, Sjoerd (Chemistry - A European Journal, 2019)
[(BDI)Mg+][B(C6F5)(4)(-)] (1; BDI=CH[C(CH3)NDipp](2); Dipp=2,6-diisopropylphenyl) was prepared by reaction of (BDI)MgnPr with [Ph3C+][B(C6F5)(4)(-)]. Addition of 3-hexyne gave [(BDI)Mg+(EtCCEt)][B(C6F5)(4)(-)]. Single-crystal X-ray analysis, NMR investigations, Raman spectra, and DFT calculations indicate a significant Mg-alkyne interaction. Addition of the terminal alkynes PhCCH or Me3SiCCH led to alkyne deprotonation by the BDI ligand to give [(BDI-H)Mg+(CCPh)](2)2[B(C6F5)(4)(-)] (2, 70%) and [(BDI-H)Mg+(CCSiMe3)](2)2[B(C6F5)(4)(-)] (3, 63%). Addition of internal alkynes PhCCPh or PhCCMe led to [4+2] cycloadditions with the BDI ligand to give Mg+C(Ph)=C(Ph)C[C(Me)=NDipp](2)(2) 2[B(C6F5)(4)(-)] (4, 53%) and Mg+C(Ph)=C(Me)C[C(Me)=NDipp](2)(2)2[B(C6F5)(4)(-)] (5, 73%), in which the Mg center is N,N,C-chelated. The (BDI)Mg+ cation can be viewed as an intramolecular frustrated Lewis pair (FLP) with a Lewis acidic site (Mg) and a Lewis (or BrOnsted) basic site (BDI). Reaction of [(BDI)Mg+][B(C6F5)(4)(-)] (1) with a range of phosphines varying in bulk and donor strength generated [(BDI)Mg+PPh3][B(C6F5)(4)(-)] (6), [(BDI)Mg+PCy3][B(C6F5)(4)(-)] (7), and [(BDI)Mg+ PtBu3][B(C6F5)(4)(-)] (8). The bulkier phosphine PMes(3) (Mes=mesityl) did not show any interaction. Combinations of [(BDI)Mg+][B(C6F5)(4)(-)] and phosphines did not result in addition to the triple bond in 3-hexyne, but during the screening process it was discovered that the cationic magnesium complex catalyzes the hydrophosphination of PhCCH with HPPh2, for which an FLP-type mechanism is tentatively proposed.
CRIS-Team WoS Importer:2019-03-01

Evidence for Charge-Transfer Mediation in the Primary Events of Singlet Fission in a Weakly Coupled Pentacene Dimer - Basel, Bettina; Zirzlmeier, Johannes; Hetzer, Constantin; Seelam, Rajagopala Reddy; Phelan, Brian T.; Krzyaniak, Matthew D.; Volland, Michel; Brana Coto, Pedro; Young, Ryan M.; Clark, Timothy; Thoss, Michael; Tykwinski, Rik; et al. (Chem, 2018)
Singlet fission (SF) is a process that converts one singlet excited state into two triplet states. The mechanism of SF is still not well understood. Here, we report on the use of a combination of transient absorption and electron paramagnetic resonance spectroscopies in conjunction with theoretical calculations to probe SF in a pentacene dimer linked by a non-conjugated, 1,4-diethynylbicyclo[2.2.2]octane spacer. Next to observing the key intermediates in solution-based SF, including the formation and decay of a quintet state that precedes formation of the pentacene triplet excitons, we demonstrate that the coupling is sufficiently weak that SF is essentially inoperative in non-polar media. Transitioning to a polar medium, however, amplifies the coupling strength such that SF becomes operative and supports long triplet lifetimes. Our results offer strong evidence for a charge-transfer mediation and, in turn, provide a solid framework for decoding the complete mechanism of SF in systems beyond pentacene.

Exfoliation of Graphene by Dendritic Water-Soluble Zinc Phthalocyanine Amphiphiles in Polar Media - Methfessel, Christian; Volland, Michel; Brunner, Kristin; Wibmer, Leonie; Hahn, Uwe; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Two zinc phthalocyanines (ZnPcs) have been equipped with Newkome-type dendritic branches of increasing size and number of terminal carboxylate functional groups. The negatively charged carboxylates render these polyelectrolytes soluble in polar media such as methanol or buffered water. Sonication of the ZnPcs with graphene allowed for pronounced non-covalent binding of the ZnPc moieties on the graphene surface. These hybrid systems were fully characterized via UV/Vis, AFM, TEM, Raman and transient absorption spectroscopy, yielding insights into the electron donating nature of the novel phthalocyanine structures.
Keywords: dendrimers; donor-acceptor system; energy transfer; exfoliation; graphene

Mono- And Tripodal Porphyrins: Investigation on the Influence of the Number of Pyrene Anchors in Carbon Nanotube and Graphene Hybrids - Garrido, Marina; Volland, Michel; Münich, Peter Wilhelm; Rodríguez-Pérez, Laura; Calbo, Joaquín; Ortí, Enrique; Herranz, M. ángeles; Martín, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
A series of molecular precursors, containing one (1 and 3) or three (2 and 4) pyrene anchors, covalently linked to porphyrins (free base or Zn), were prepared and characterized. All of them enable their π-πstacking onto low-dimensional nanocarbons including single-walled carbon nanotubes (SWCNTs) and nanographene (NG), their individualization, and their characterization. Microscopic (TEM, AFM) and spectroscopic (steady-state UV-vis and fluorescence, spectroelectrochemistry, and transient absorption measurements) techniques were at the forefront of the characterizations and were complemented by Raman spectroscopy and theoretical calculations. Of great importance is the Raman analysis, which corroborated n-doping of the nanocarbons due to the interactions with 1-4 when probed in the solid state. In solution, the situation is, however, quite different. Efficient charge separation was only observed for the graphene-based system NG/3.
CRIS-Team Scopus Importer:2020-02-04

Nanographene favors electronic interactions with an electron acceptor rather than an electron donor in a planar fused push-pull conjugate - Volland, Michel; Zhou, Ping; Wibmer, Leonie; Haener, Robert; Decurtins, Silvio; Liu, Shi-Xia; Guldi, Dirk Michael (Nanoscale, 2019)
A combination of a preexfoliated nanographene (NG) dispersion and fused electron donor-acceptor tetrathiafulvalene-perylenediimide (TTF-PDI) results in a noncovalent functionalization of NG. Such novel types of nanohybrids were characterized by complementary spectroscopic and microscopic techniques. The design strategy of the chromophoric and electroactive molecular conjugate renders a large and planar -extended system with a distinct localization of electron-rich and electron-poor parts at either end of the molecular conjugate. Within the in situ formed nanohybrid, the conjugate was found to couple electronically with NG preferentially through the electron accepting PDI rather than the electron donating TTF and to form the one-electron reduced form of PDI, which corresponds to p-doping of graphene.
CRIS-Team WoS Importer:2019-03-15

Novel nanographene/porphyrin hybrids-preparation, characterization, and application in solar energy conversion schemes - Kießling, Daniel; Costa, Ruben Dario; Katsukis, Georgios; Malig, Jenny; Lodermeyer, Fabian; Feihl, Sebastian; Roth, Alexandra Marina; Wibmer, Leonie; Kehrer, Matthias; Volland, Michel; Wagner, Pawel; Wallace, Gordon G.; et al. (Chemical Science, 2013)
Four novel nanographene/porphyrin hybrids were prepared, characterized, and probed in solar energy conversion schemes. Exfoliation of graphite by means of immobilizing four different porphyrins onto the basal plane of graphene is accompanied by distinct electronic interactions in both the ground and the excited states. In the ground state, a strong loss in oscillator strength goes hand-in-hand with a notable broadening of the porphyrin transitions and, as such, attests to the shift of electron density from the electron donating porphyrins to nanographene. In the excited state, a nearly quantitative quenching of the porphyrin fluorescence is indicative of full charge transfer. The latter is corroborated by femtosecond transient absorption measurements, which reveal the generation of the one-electron oxidized radical cation of the porphyrins with absorption maxima at 490 and 625 nm in the visible region and conduction band electrons in nanographene with features at 890 and 1025 nm in the near infrared region. We have demonstrated the applicability of the new nanographene/porphyrin hybrids in, for example, solar cells. In this regard, the presence of flakes is crucial in terms of influencing the injection processes, preventing aggregation, and reducing recombination losses, which are commonly encountered in porphyrin-based DSSCs. © 2013 The Royal Society of Chemistry.

The Cascade Reactions of Indigo with Propargyl Substrates for Heterocyclic and Photophysical Diversity - Mccosker, Patrick M.; Butler, Nicholas M.; Shakoori, Alireza; Volland, Michel; Perry, Matthew J.; Mullen, Jesse W.; Willis, Anthony C.; Clark, Timothy; Bremner, John B.; Guldi, Dirk Michael; Keller, Paul A. (Chemistry - A European Journal, 2021)
The synthesis of structurally diverse heterocycles for chemical space exploration was achieved via the cascade reactions of indigo with propargylic electrophiles. New pyrazinodiindolodione, naphthyridinedione, azepinodiindolone, oxazinoindolone and pyrrolodione products were prepared in one pot reactions by varying the leaving group (-Cl, -Br, -OMs, -OTs) or propargyl terminal functionality (-H, -Me, -Ph, -Ar). Mechanistic and density functional theory studies revealed that the unsaturated propargyl moiety can behave as an electrophile when aromatic terminal substitutions are made, and therefore competes with leaving group substitution for new outcomes. Selected products from the cascade reactions were investigated for their absorption and fluorescence properties, including transient absorption spectroscopy. This revealed polarity dependent excited state relaxation pathways, fluorescence, and triplet formation, thus highlighting these reactions as a means to access diverse functional materials rapidly.
CRIS-Team WoS Importer:2021-03-05

Tuning the Carbon Nanotube Selectivity: Optimizing Reduction Potentials and Distortion Angles in Perylenediimides - Münich, Peter Wilhelm; Schierl, Christoph; Dirian, Konstantin; Volland, Michel; Bauroth, Stefan; Wibmer, Leonie; Syrgiannis, Zois; Clark, Timothy; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2018)
Different water-soluble perylenediimides (PDIs) have been used to individualize and stabilize single-walled carbon nanotubes (SWCNTs) in aqueous media. A key feature of the PDIs is that they can be substituted at the bay positions via the addition of two and/or four bromines. This enables control over structural and electronic PDI characteristics, which prompted us to conduct comparative assays with focus on SWCNTs' chirality and charge transfer. Electrochemical, microscopic, and spectroscopic experiments were used to investigate the SWCNT chiral selectivity of PDIs, on the one hand, and charge-transfer reactions between SWCNTs and PDIs, on the other hand.